Research of the Key Technology of the Drive Reducer Localization for Copper Melting Furnace - Feng Yimin; Fan Naiqian (Jixie chuandong, 2015)
In order to solve the problem that reducer is overheating and the spin current is too large when the reducer of copper melting furnace operating,through the analysis of carrying capacity of imported reducer worm gear and worm drive,the measure to improve the transmission capacity is proposed,and the appropriate readjustment of the worm gear pair center distance is carried out. In addition,for maintaining the connection dimensions of homebred reducer consistent with imported reducer,the sizes of the reducer box are adjusted and optimized. In order to improve the contact area of worm gear pair,the scraping- grinding and running- in with heavy load are combined,and as a result,the quality of contact pattern is improved plentifully and the homebred reducer runs smoothly with a low current.